Influence of invasive aspergillosis during acute leukaemia treatment on survival after allogeneic stem cell transplantation: a prospective study of the EBMT Infectious Diseases Working Party - Penack, Olaf (Netherlands, 2025)
Background
Infections are the main reason for mortality during acute leukaemia treatment and invasive aspergillosis (IA) is a major concern. Allogeneic stem cell transplantation (alloSCT) is a standard therapy and often is the only live-saving procedure in leukaemia patients. The profound immunodeficiency occurring after alloSCT led to high IA-associated mortality in the past. Therefore, patients with IA were historically considered transplant-ineligible. Recently, there has been improvement of anti-fungal management including novel anti-fungal agents. As a result, more leukaemia patients with IA are undergoing alloSCT. Outcome has not been prospectively assessed.
Methods
We performed a prospective study in acute leukaemia patients undergoing alloSCT to analyse the impact of a prior history of probable or proven IA (pre-SCT IA). The primary endpoint was 1-year non-relapse mortality (NRM). Relapse free survival and overall survival were analysed as secondary endpoints.
Findings
1439 patients were included between 2016 and 2021. The incidence of probable or proven pre-SCT IA was 6.0% (n = 87). The cumulative incidence of 1-year NRM was 17.3% (95% CI 10.2–26.0) and 11.2% (9.6–13.0) for patients with and without pre-SCT IA. In multivariate analyses the hazard ratio (HR) for 1-year NRM was 2.1 (1.2–3.6; p = 0.009) for patients with pre-SCT IA. One-year relapse-free survival was inferior in patients with pre-SCT IA (59.4% [48.3–68.9] vs. 70.4 [67.9–72.8]; multivariate HR 1.5 [1.1–2.1]; p = 0.02). Consequently, 1-year overall survival was lower in patients with pre-SCT IA: (68.8% [57.8–77.4] vs. 79.0% [76.7–81.1]; multivariate HR 1.7 [1.1–2.5]; p = 0.01).
Interpretation
Pre-SCT IA remains to be significantly associated with impaired alloSCT outcome. On the other hand, more than two thirds of patients with pre-SCT IA were alive at one year after alloSCT. IA is not anymore an absolute contraindication for alloSCT because the majority of patients with IA who undergo alloSCT benefit from this procedure.